The influence of the media on children's language - Dulaj, Fridrik (Technium Social Sciences Journal, 2022)
Our paper aims to point out the sociolinguistic relations between the Albanian Language dialects and Standard Albanian. The focus of our research are school environments. The roads construction and the freedom of movement inside and outside Kosovo, especially the close relations with Albania and the TV platforms Digitalb and Tring being important sociolinguistic factors have brought closer the sweetness of Albanian Language to Albanians. Therefore, this paper will elaborate the role and connection of these factors in language. TV channels as Bang Bang, T, Tring Tring, Tring Albania, Discovery Science, Tring History, Tring Nature, or the TV program “Albanian Tracks” led by Marin Mema are educational programs that spread general knowledge in different fields like: nature, history, etc. In larger schools, especially in classrooms where students come from different countries, we notice language systems and subsystems which interact in children’s general communication.